Peran Perbankan Syariah dalam Pemberdayaan UMKM Pedagang Garam di Pamekasan Madura - Alvan Fathony; Jamilatul Mahyah (Universitas Galuh, 2023)
Islamic banking, as the main figure in the Islamic financial institution, strives to become an intermediary institution in incorporating Islamic finance into salt traders. Salt farmers who enter into a cooperation agreement (mudarabah) will share the proceeds at a later date according to the agreed-upon terms, where the landowners will receive 75% of the sales proceeds and 25% will be allocated to the land workers. This study aims to determine the role of Islamic banking in empowering small and medium-sized enterprises (SMEs) of salt traders. The rising prices of salt in the market will result in a depletion of salt stock in the warehouses and require a significant amount of capital. Traders will need a substantial amount of working capital to meet the demands of their businesses. They will borrow the necessary capital according to their needs, to repay it by the agreed-upon terms. This research utilizes a qualitative descriptive method, and the primary data used in this study are obtained through a literature review and interviews. The instrument used for collecting primary data is interviews conducted with salt trader community members in Galis Pamekasan. They revealed that Islamic banking also plays a role in the development of salt trader SMEs by assisting in the implementation of government programs such as the People's Business Credit (KUR), financing distribution, profit sharing, and savings and loans.